THE MINERAL AND PETROLEUM RESOURCES DEVELOPMENT ACT 28 OF 2002 AND THE ENVIRONMENT - PJ Badenhorst; RT Stein (Obiter, 2022)
The provisions aimed at the management and protection of the environment contained in the Minerals and Petroleum Resources Development Act are discussed in this article. A combination of “command-and-control” and “management planning” regulatory techniques are employed in the Act, creating relatively stringent environmental management and protection obligations throughout the life-cycle of reconnaissance, prospecting and mining operations.